A Study Of The Economic Supporting Capacity Of New Landfill In The Western Region Of Bojonegoro Regency - Wijayanti, Dwi; Firdausi, Rizal Zubad; Budianto, Agus (IDFoS Indonesia, 2021)
There are always problems caused by waste at various regional levels, starting from the village, sub-district, district/city levels even at the national and state levels. The rate of population growth is increasing rapidly which has an impact on increasing the amount of waste. The Landfill for waste in Bojonegoro Regency had been overloaded since 2019, which in 2020 will operate a new Landfill in the western region. Improper planning will be able to cause financial losses but on the contrary if done with proper planning it will create opportunities to advance the economy for the surrounding community. The supporting capacity of the Landfill is an important thing that had to be considered in planning the development and operation of the Landfill, in order to be able to support the activities of using the landfill in a sustainable manner. The purpose of this research was to find out whether the new Landfill was feasible to operate by considering the estimated costs incurred and the income earned. The calculation of the economic supporting capacity was carried out using the Landfill economic valuation method. The results of the calculation of the economic carrying capacity of the new landfill had a benefit cost ratio (BCR) of 1.16, with an IRR value of 35.48% so that the New landfill activity was feasible to carry out.